Public Spectacles, Private Narratives: Canadian Heritage Campaigns, Maternal Trauma and the Rise of the Koffort (trunk) in Icelandic-Canadian Popular Memory - Bertram, Laurie K. (Material Culture Review, 2010)
The late rise of the previously undervalued migrant trunk, or "koffort" within Icelandic-Canadian popular culture is easily linked to the proliferation of migration-focused visual heritage campaigns in Canada from 1967 onwards. This corresponding re-emergence in local art and museums, as well as in family homes, suggests that Icelandic-Canadians have simply adopted the static, celebratory image of migration history set forth by the state. However, by using interviews and photographs detailing the mnemonic uses of these objects in private, this article contends that the trunk is a hybrid object that offers families archives and points of contact for histories of trauma that also draw from traditional Icelandic notions of fatalism and matrilineal systems of identification. Despite its redemptive public image, the trunk is often the vehicle through which are revealed female-centred narratives of migrant trauma—spousal abuse, widowhood and infant mortality. Rather than delivering a cohesive vision of settler nationalism to Canadians, the migrant trunk has emerged as a powerful, but unsettling archive in popular practice. Résumé L’engouement tardif pour ce qui était autrefois un objet dévalorisé, la malle de bois des migrants, ou «  koffort  », au sein de la culture populaire des Islandais du Canada peut se lier aisément à la prolifération des campagnes en faveur du patrimoine visuel centré sur la migration au Canada depuis 1967. Le fait que cet objet ait réapparu, de manière correspondante, dans les musées et les arts locaux, ainsi que dans les familles, laisse penser que les Islandais du Canada n’ont fait qu’adopter l’image commémorative statique de l’histoire telle qu’elle a été instaurée par l’État. Cependant, en se basant sur des entrevues et des photographies qui détaillent les usages mnémoniques de ces objets en privé, cet article permet au contraire d’avancer que la malle est un objet hybride qui présente des archives familiales et des points de contact pour des histoires traumatiques qui s’inspirent également des notions islandaises traditionnelles de fatalité et de systèmes d’identification matrilinéaires. Malgré son image publique rédemptrice, la malle est souvent le véhicule par lequel se révèlent les récits, centrés sur les femmes, des traumatismes vécus par les migrants – abus commis par le conjoint, veuvage et mortalité infantile. Plutôt que de donner aux Canadiens une image de cohésion nationale des colons, la malle des migrants est apparue comme un élément d’archive puissant mais dérangeant dans la pratique populaire.